"You Are Going to School": Exploring the Precollege Experiences of First-Year Black Males in Higher Education. Issue 1 (January 2021) - Hines, Erik M.; Mayes, Renae D.; Hines, Mia R.; Henderson, Jerrod A.; Golden, Monique N.; Singleton, Paul; Cintron, Dakota W.; Wathen, Bobbi-Jo; Wright, Christopher G.; Vega, Desireé; Slack, Tyron
Black males are often underrepresented in postsecondary education settings and frequently encounter many barriers in getting to college. Our aim in this qualitative investigation was to understand the precollege and college experiences of Black males who successfully enrolled in a postsecondary institution. Through a focus group interview, seven Black males in a living and learning community shared their experiences prior to and during enrollment at a highly selective, predominantly White institution. We used the grounded theory approach (Strauss & Corbin, 1998 ) to analyze the focus group data and pinpoint thematic explanations of precollegiate and collegiate experiences of Black males. Based on the thematic findings, we offer specific recommendations on how school counselors can help Black males prepare and eventually matriculate in higher education.